STUDI PELAKSANAAN PENDEKATAN SAINTIFIK PADA PROSES PEMBELAJARAN SOSIOLOGI DI SMA NEGERI SE-KOTA PONTIANAK - Junarso Junarso; Sulistyarini Sulistyarini; Supriadi Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to study the implementation of the scientific approach to teaching and learning Sociology in Senior High Schools in Pontianak City. The form of research was is quantitative with a descriptive approach. All Sociology teachers from 10 schools were taken as the population. Twelve instructors who have implemented the Curriculum of 2013 were taken as the sample. The data collection techniques used are survey and documentation, as well as the data collection tools used are questionnaires, notes, and archives. The data collected were calculated using SPSS 18.0. The descriptive hypothesis test used was one sample t-test testing to verify whether or not a specific value (as a comparison) is significantly different from the average of a sample. The data analysis was presented in percentages. The findings showed that the alternative hypothesis (Ha ) was approved. The Scientific Approach in Sociology teaching and learning in High Schools in Pontianak City has been implemented with an average of 87.84%, categorized as very good. Keywords: Scientific Approach, Teaching and Learning Sociology